PENGEMBANGAN E-MODUL MATERI PECAHAN BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) KELAS V SD/MI - Marhamah Marhamah; Tanzimah Tanzimah; Asnurul Isroqmi (IKIP Siliwangi, 2022)
This study aims to produce valid, practical e-modul on grade V SD/MI fraction materials, and to determine the effectiveness of the e-modules that have been developed. This research is a development research using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The object of this research is the quality of e-modules based on Contextual Teaching and Learning (CTL) in the material of fractions for class V SD/MI that was developed. Data collection techniques by observation, questionnaires and tests. Data analysis techniques in this study are validity analysis, practicality analysis and effectiveness analysis. Based on the results of the study indicate that the developed e-module can be declared valid based on the assessment of media experts with an average score of 3.1; material expert assessment with an average score of 3.2; and obtained very valid criteria based on the assessment of educators with an average score of 3.7. E-Modules are also stated to be very practical based on student response questionnaires with a total average score of 3.5 and the results of learning observations of 86%; and the e-module was declared very effective based on the student learning outcomes test with a percentage of 82%.